Ethnic Structure of St Petersburg – Petrograd – Leningrad in the Period of 1703-1991 - Garczyk, Bartłomiej (Studia Historiae Oeconomicae, 2013)
This article presents a multinational and multireligious character of St. Petersburg since the founding of the city to the collapse of the Soviet Union. An ethnic and cultural mosaic was also an important feature in other centers of Russia, including Moscow and Odessa, as well as forming part of the national capital of the Russian Empire in Warsaw, Riga and Tallinn. St. Petersburg is a city but of a symbolic and unique character. It is the subject of literary impressions and creative inspiration for generations of artists. In addition, St. Petersburg - Petrograd - Leningrad was the capital of a multinational and multireligious Russian Empire, Soviet Russia, and since 1918, it was the second most important city of the Soviet Union. The author’s intention is also to present the history of St. Petersburg - Petrograd - Leningrad, as seen through the prism of the history of national minorities living in it.